Pemanfaatan Limbah Padat Organik Rumah Tangga Menjadi Eko-Enzim Melalui Peningkatan Keterampilan Kelompok Masyarakat Dusun Karya Maju, Muaro Jambi: Utilization of Household Organic Solid Waste into Eco-Enzymes through Skill Improvement of Community Groups in Karya Maju Hamlet, Muaro Jambi - Juita, Febri; Rodhiyah, Zuli; Laura Christina Hutagalung, Winny; Yanova, Shally (Universitas Jambi, 2024)
Household organic solid waste is a type of waste that comes from leftover food, vegetables, fruit, dry leaves and other organic materials resulting from daily activities. Household organic waste can cause environmental problems if not managed properly. Eco-enzymes are a mixture of enzymes made from organic materials such as food waste, fruits, vegetables and water. Eco-enzymes can be used as household cleaners, organic fertilizers, or even as medicines. Therefore, this service activity aims to introduce the processing of domestic organic waste into eco-enzymes. The method used is an experiment in making eco-enzymes as well as a scientific approach to what mothers need to solve household waste problems. Eco-enzymes use the principle of a fermentation process over a period of 3-6 months. The service was carried out in the women's yasinan group consisting of around 47 members in Karya Maju District. Based on a preliminary survey, it was discovered that the domestic organic solid waste there had never been processed and was simply thrown away. For this reason, the service team provides counseling and workshops regarding the management of organic solid waste into multi-purpose eco-enzymes. Apart from that, the team also provided equipment to make eco-enzymes. Based on survey results before and after socialization, there was an increase in residents' knowledge and desire to process organic waste into eco-enzymes